Framework for decentralised architectural design BIM and Blockchain integration. (June 2021) - Dounas, Theodoros; Lombardi, Davide; Jabi, Wassim
The paper introduces a framework for decentralised architectural design in the context of the fourth industrial revolution. We examine first the constraints of building information modelling in regard to collaboration and trust. We then introduce Blockchain infrastructure as a means for creating new operational and business models for architectural design, through project governance, scaling collaboration nominally to thousands of agents, and shifting trust to the infrastructure rather than the architectural design team. Through a wider consideration of Blockchains in construction projects we focus on the design process and validate our framework with a prototype of BIM design optimisation integrated with a Blockchain mechanism. The paper concludes by outlining the contributions our framework can enhance in the building information modelling processes, within the context of the fourth industrial revolution.